2014
DOI: 10.1186/2048-7010-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Climate-smart soil water and nutrient management options in semiarid West Africa: a review of evidence and analysis of stone bunds and zaï techniques

Abstract: There is an increasing need for West African Sahel farmers to be availed with appropriate technologies and management practices that sustainably increase productivity and resilience, while reducing greenhouse gas emissions where possible. In this paper, we analysed prevailing key water and nutrient interaction practices namely stone bund, zaï and half-moon techniques in order to explore how their outcomes could be linked to climate change adaptation and mitigation. Data were derived from previous publications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
81
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 17 publications
1
81
0
3
Order By: Relevance
“…Because of unpredictable rainfall [18] and decreased agricultural productivity, many soil and water conservation technologies such as stone lines, half-moons, contour hedgerows, rock bunds, filter walls, zaï, agroforestry, contour ridges, benches and no-tillage have been developed and are now widespread [19][20][21][22][23]. Tested technologies have shown that they can reduce runoff [16,[24][25][26] and soil erosion [27][28][29], improve water infiltration [12,22,30] and increase soil moisture [20,23,[31][32][33]. However, their adoption did not always meet the expectations probably due to the promotion of a limited number of options everywhere as if "one size fits all. "…”
Section: Open Accessmentioning
confidence: 99%
“…Because of unpredictable rainfall [18] and decreased agricultural productivity, many soil and water conservation technologies such as stone lines, half-moons, contour hedgerows, rock bunds, filter walls, zaï, agroforestry, contour ridges, benches and no-tillage have been developed and are now widespread [19][20][21][22][23]. Tested technologies have shown that they can reduce runoff [16,[24][25][26] and soil erosion [27][28][29], improve water infiltration [12,22,30] and increase soil moisture [20,23,[31][32][33]. However, their adoption did not always meet the expectations probably due to the promotion of a limited number of options everywhere as if "one size fits all. "…”
Section: Open Accessmentioning
confidence: 99%
“…As there are huge variations between geographic locations and socio-economic conditions in terms of risks to be faced and capacities to face them, CSA thrives to engage context-specific and locally adapted actions and interventions, along the whole agricultural value chain [7]. In the same line, it is believed that the management of natural and human resources of agricultural production at the very local level determines the success or failure in closing the yield gap [14].…”
mentioning
confidence: 98%
“…In the region, although soil fertility is known as one of the major challenges faced by agriculture [5,6], climate change and variability add extra burdens [4]. Indeed, the livelihoods of people in the region depend on rain-fed agriculture and livestock [7], which are known to be the most vulnerable to climate change [8,9] with serious threats to food security.…”
mentioning
confidence: 99%
“…Zougmoré et al [25] argued that loss of water through run-off, soil evaporation and drainage below the root zone account for the water deficiency (longer periods of water stress). This water, however, if managed properly could easily be used to recharge shallow wells to enhance the groundwater storage.…”
mentioning
confidence: 99%
“…The commonly applied field level technologies include live fencing and grass strips [11], compost with mineral fertilizers [19,20], zaï or pit planting with organic amendments [21,22], stone and contour bunding [23,24], halfmoon techniques [21,25] and gully interventions [11]. However, these methods were piecemeal efforts that did not evolve into precise and efficient soil degradation control measures as they are labour-intensive and, with the increasing annual levels of degradation, only translated into marginal yield increase that is not sustainable [26].…”
mentioning
confidence: 99%